Incorporation of fish protein concentrates from scoliodon palasorrah (cuvier) and decapterus macrosoma (bleeker) in cropeck. - Espejo, Jasmin M. (Diliman, Quezon City College of Fisheries, University of the Philippines, 1974)
This study was made on shark, Scoliodon palasorrah (Cuvier), and roundscad, Decapterus macrosoma (Bleeker). Emphasis was given on the possibility of incorporating the fish protein concentrates from shark and roundscad to kroepeck. Results on the proximate analyses of fish protein concentrates showed that the percentages of protein, ash and moisture from shark were higher than that of roundscad. The different methods of preparation of the fish protein concentrates from the 2 species affected their protein contents. The results obtained in the proximate analyses of fish protein concentrate incorporation in kroepeck show that the protein level of the fortified product increased, the moisture and ash contents obtained were lower than that of the unfortified korepeck. In the analysis of variance on the consumer preference test, results obtained show that at 5% level of significance, difference existed among the treatments. Treatment C (galonggong) turned out to be the least preferred by the panelists. In the consumer acceptance test, results showed that no significant difference existed among the treatment and replicates at 5% and 1% level. This showed that the panelists equally accepted the fortified and unfortified products.
Special Problem (Undergraduate. Bachelor of Science in Fisheries ) Fisheries Technology, College of Fisheries, University of the Philippines, 1974.
Keywords: Scoliodon palasorrah (cuvier) Decapterus macrosoma (bleeker)